Prospects For the use of Biomass Energy Sources - Zayliddinovna, Sayfiddinova Hikmatxon; ugli, Sultonov Sordor Soloxiddin (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, the biomass energy calculated from non-traditional sources of energy in the current period of energy shortage and its formation, biomass energy types, technologies of its use, preparation processes, biological waste as a source of energy are overthrown methods.